2013
DOI: 10.2478/s11686-013-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Human dirofilariasis due to Dirofilaria repens in Ukraine, an emergent zoonosis: epidemiological report of 1465 cases

Abstract: The filarial nematode Dirofilaria repens is currently considered to be one of the most extensively spreading human and animal parasites in Europe. In Ukraine, reporting cases of dirofilariasis has been mandatory since 1975, and the disease was included in the national surveillance system for notifiable diseases. Up until December 31st 2012, a total of 1533 cases have been registered, with 1465 cases occurring within the previous 16 years. Most of the cases of dirofilariasis were registered in 6 regions: Kyiv, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 16 publications
1
74
0
3
Order By: Relevance
“…As observed by other authors, visual status usually remained intact after surgical removal of the worm (Koltas et al, 2002;Maraghi et al, 2006;Mittal et al, 2008;Argy et al, 2011;Otranto et al, 2011a;Otranto et al, 2011b). Diagnosis of human dirofilariosis is primarily based on histological evaluation of infected tissue and the macroscopic characteristics of the worm (Rouhani & Athari, 2003;Nath et al, 2010;Tafti et al, 2010;Argy et al, 2011;Otranto et al, 2011b). Confirmation of morphological identification and definite diagnosis of D. repens is possible by DNA analysis with polymerase chain reaction (Vakalis et al, 1999) and primers for a highly specific portion of COI gene.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As observed by other authors, visual status usually remained intact after surgical removal of the worm (Koltas et al, 2002;Maraghi et al, 2006;Mittal et al, 2008;Argy et al, 2011;Otranto et al, 2011a;Otranto et al, 2011b). Diagnosis of human dirofilariosis is primarily based on histological evaluation of infected tissue and the macroscopic characteristics of the worm (Rouhani & Athari, 2003;Nath et al, 2010;Tafti et al, 2010;Argy et al, 2011;Otranto et al, 2011b). Confirmation of morphological identification and definite diagnosis of D. repens is possible by DNA analysis with polymerase chain reaction (Vakalis et al, 1999) and primers for a highly specific portion of COI gene.…”
Section: Discussionmentioning
confidence: 91%
“…Infectious stage -third larval stage is transmitted by mosquitoes of genera Aedes, Culex, Anopheles, etc., that commonly occur in the Slovak region. The first diagnosed autochthonous canine dirofilariosis in Slovakia was caused by D. repens in 2005 (Svobodová et al, 2005), and in 2007 the first case of human subcutaneous dirofilariosis was identified in the patient from western Slovakia, who has never travelled abroad (Babál et al, 2008). Since the year 2007, 4 cases of human subcutaneous dirofilariosis caused by D. repens in Slovakia have been reported in total (Babál et al, 2008;Ondriska et al, 2010;Nováková et al, 2011;Hrčková et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increasing number of publications on this topic on the territory of Ukraine and Russia. Human dirofilariosis was registered in Croatia, Slovenia, Hungary (2,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Dirofilariasis is an important vector-borne and globally distributed zoonotic disease [1][2][3] and it is a single vector-born disease caused by a nematode in the Russian Federation [4]. The disease is caused by roundworms in the genus Dirofilaria (Nematoda: Onchocercidae) and is naturally transmitted by mosquitoes.…”
Section: Introductionmentioning
confidence: 99%